Border surveillance: biometric technologies and personal data in Latin American migration - Murrugarra Retamozo, Brenda Isabel (2024)
The study aims to understand how the development of biometric technologies and systems by the U.S. Government surveils migrants and asylum seekers from Latin America. In the methodology, I applied a qualitative approach with a descriptive level. I used the observation technique for the conference on migration and surveillance in Latin America, and the notebook as an instrument. Also, I used the documentary analysis technique, with the paraphrase card instrument for the five (5) scientific articles related to migration and surveillance. The results I obtained show that: (i) the use of biometric technologies at the U.S.-Mexico border by the U.S. Government would present risks to the fundamental rights of migrants and asylum seekers from Latin America, such as the right to privacy, (ii) the collection of biometric data through the CBP One application would facilitate the surveillance of migrants and asylum seekers from Latin America, and (iii) the exchange of biometric data that would be taking place between the U.S. Government and the Latin American Governments, would constitute a critical violation of the fundamental rights of migrants and asylum seekers from Latin America. I concluded that the use of biometric technology for surveillance purposes, which the U.S. Government would carry out or would intend to carry out on migrants and asylum seekers from Latin America, would constitute a serious violation of the fundamental rights of this group.